1985
DOI: 10.1007/bf00134352
|View full text |Cite
|
Sign up to set email alerts
|

A portfolio of risk measures

Abstract: A comprehensive set of sixteen measures of willingness to take risks has been developed. This set includes measures from three categories: measures from standardized risky situations having an underlying theory of risk, measures inferred from revealed choices in financial decisions, and measures derived from attitudes. A study of over 500 top-level business executives shows significant relationships within categories, but relatively little relationship across categories. Context differences, especially persona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(48 citation statements)
references
References 32 publications
1
46
0
1
Order By: Relevance
“…We also asked whether they characterized the issue as a positive or a negative situation (Jackson & Dutton, 1988;MacGrimmon & Wehrung, 1985;Sitkin & Weingart, 1995). Cronbach's a for the risk perception construct is 0.81.…”
Section: Dependent Variablementioning
confidence: 99%
“…We also asked whether they characterized the issue as a positive or a negative situation (Jackson & Dutton, 1988;MacGrimmon & Wehrung, 1985;Sitkin & Weingart, 1995). Cronbach's a for the risk perception construct is 0.81.…”
Section: Dependent Variablementioning
confidence: 99%
“…Specific risk tolerance is described as a dispositional tendency to take or avoid risks in a specific situation, which is different from general risk tolerance where people exhibit stable preferences over a variety of situations. In a consumer context, 'preference for risk' was significant in predicting choice under risk and early work on a portfolio of risk measures found some support for a concept of risk tolerance as an individual difference (Zickar and Highhouse, 1998), since differences among individuals were stronger than differences in the various measures for a single individual (MacCrimmon and Wehrung, 1985). In contrast, Pablo (1997) found that personality factors did not emerge as a significant determinant of an individual's willingness to take risks; and Schoemaker (1990) found low correlations within individuals across decision domains.…”
Section: Consumer Tolerance Of Food Riskmentioning
confidence: 99%
“…Researchers disagree on the extent to which managerial risk propensity influences managerial behavior. MacCrimmon and Wehrung (1985) state that though risk propensity is a stable trait, willingness to take risks varies across contexts, particularly across contexts that are perceived as opportunities rather than threats. In our context of new technology deployment, we note that the exploration of new routines is generally associated with greater risk taking than is exploitation (March 1991).…”
Section: Risk-taking-caution Cognitive Style and New Technology Deplomentioning
confidence: 98%